Provider perspectives on the impact of COVID-19 on treatment of substance use and opioid use disorders among American Indian and Alaska Native adults - Richardson, Meenakshi; Hirchak, Katherine; Bajet, Kelsey; Brigman, Mariah; Shaffer, Racquel; Keyes, Beverly; Oliver, Karen Anderson; Kropp, Frankie; McDonell, Michael G.; Venner, Kamilla L.; Campbell, Aimee N. C. (Frontiers in Public Health, 2024)
Introduction: American Indian/Alaska Native (AI/AN) communities are more likely to suffer negative consequences related to substance misuse. The COVID-19 pandemic exacerbated the opioid overdose crisis, in combination with ongoing treatment barriers resulting from settlercolonialism, systemic oppression and racial discrimination. AI/AN adults are at greatest risk of COVID-19 related serious illness and death. In collaboration with an Indigenous community advisory board and Tribal leadership, this study explored AI/AN treatment providers' perception of client-relatives' (i.e., SUD treatment recipients) experiences during the pandemic from 2020-2022. Methods: Providers who underwent screening and were eligible to participate (N=25) represented 6 programs and organizations serving rural and urban areas in Washington, Utah, and Minnesota. Participants engaged in audio-recorded 60-90 minute semi-structured individual interviews conducted virtually via Zoom. The interview guide included 15 questions covering regulatory changes, guidance for telemedicine, policy and procedures, staff communication, and client-relatives' reactions to implemented changes, service utilization, changes in treatment modality, and perceptions of impact on their roles and practice. Interview recordings were transcribed and de-identified. Members of the research team independently reviewed transcripts before reaching consensus. Coding was completed in Dedoose, followed by analyses informed by a qualitative descriptive approach. Results: Five main themes were identified related to client-relative experiences during the COVID-19 pandemic, as observed by providers: 1) accessibility, 2) co-occurring mental health, 3) social determinants of health, 4) substance use, coping, and harm reduction strategies, and 5) community strengths. Providers reported the distinctive experiences of AI/AN communities, highlighting the impact on client-relatives, who faced challenges such as reduced income, heightened grief and loss, and elevated rates of substance use and opioid-related poisonings. Community and culturally informed programming promoting resilience and healing are highlighted. Conclusion: Findings underscore the impact on SUD among AI/AN communities during the COVID-19 pandemic. Identifying treatment barriers and mental health impacts on clientrelatives during a global pandemic can inform ongoing and future culturally responsive SUD prevention and treatment strategies. Elevating collective voice to strengthen Indigenous informed systems of care to address the gap in culturally-and community-based services, can bolster holistic approaches and long-term service needs to promote SUD prevention efforts beyond emergency response efforts.